Public health genomics in Europe (Italian Journal of Public Health, 2006)
The challenge of integrating genomics into public health The Human Genome Project was completed in 2003. Expectations are high that new knowledge and technologies arising from the project will soon contribute to the improvement of individual and population health. Yet, approaches in public health have so far not broadly used molecular knowledge of individual genetic susceptibility for achieving their goals. However, in the past decade there has been increasing awareness that advances in genomics can be utilised in public health in the near future. It is our opinion that it is of major importance to start discussion of this option and its possible consequences early enough. This thematic issue starts from the premise that public health approaches can and should no longer ignore the advances made in genomics.We are seeing the emergence of the multidisciplinary field of public health genomics that deals with these opportunities and challenges. According to the statements of an expert group that discussed public health genomics concepts in Bellagio in 2005, public health genomics can be defined as:“The responsible and effective translation of genome-based knowledge and technologies for the benefit of population health (Bellagio Report).”